INCORPORATION OF POLYHERBAL FORMULATION INTO THERAPEUTIC COOKIES FOR THE MANAGING DISORDERS OF CARBOHYDRATE AND LIPID DYSREGULATION: Polyherbal Cookies for Metabolic Syndrome Management - FAUZIA BANO; SEEMA KANOJIA; ARVIND K. SRIVASTAVA (The Bioscan, 2026)
The increasing consumer demand for health-promoting foods has intensified research on functional ingredients with potential nutraceutical benefits. In the present investigation, a polyherbal formulation (PF) was incorporated into cookies to develop a value-added functional food with enhanced nutritional and therapeutic attributes. The PF comprised Olea europaea (leaves), Momordica charantia (fruit), Enicostemma littorale (leaves), Gymnema sylvestre (leaves), Cinnamomum zeylanicum (bark), Garcinia indica (fruit), Hibiscus rosa-sinensis (flower), and Emblica officinalis (fruit), selected based on their documented hypoglycemic and hypolipidemic properties. The developed formulations were subjected to proximate composition analysis following standard protocols, alongside sensory evaluation using a hedonic scale. Incorporation of PF resulted in the enhancement in protein and dietary fiber content, accompanied by a reduction in crude fat and available carbohydrate fractions. These compositional modifications indicate improved nutritional quality. Sensory attributes remained within acceptable limits across optimized formulations, supporting consumer acceptability. Overall, the findings substantiate the feasibility of incorporating polyherbal blends into bakery products as a strategy for developing functional foods with potential applications in the management of metabolic disorders. Such formulations also provide a platform for the integration of traditional phyto-therapeutic knowledge into modern food systems